2022
DOI: 10.1136/bmjopen-2021-059068
|View full text |Cite
|
Sign up to set email alerts
|

How do Europeans quit using tobacco, e-cigarettes and heated tobacco products? A cross-sectional analysis in 28 European countries

Abstract: ObjectivesWhile smoking tobacco remains a substantial cause of harm in Europe, novel products such as electronic cigarettes or e-cigarettes (ECs) and heated tobacco products (HTPs) have entered the market recently. While debate still persists over the role of these novel products, they are now in widespread use. This study aimed to explore the prevalence and methods of attempts to quit EC and HTP.SettingWe analysed the 2020 Eurobarometer survey, which collected data in 28 European countries.ParticipantsA repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
4
2
Order By: Relevance
“…The most frequently used aids were: first pharmacotherapy and second e-cigarettes. Those aged 15-24 were less likely to use pharmacotherapy and more likely to use e-cigarettes than those aged �55 years [11]. These results are roughly comparable to what was described by the same survey in 2017 [12].…”
Section: Discussionsupporting
confidence: 83%
“…The most frequently used aids were: first pharmacotherapy and second e-cigarettes. Those aged 15-24 were less likely to use pharmacotherapy and more likely to use e-cigarettes than those aged �55 years [11]. These results are roughly comparable to what was described by the same survey in 2017 [12].…”
Section: Discussionsupporting
confidence: 83%
“…Intentions to quit smoking are a key precursor to quitting smoking cessation; hence, it is important to evaluate the effects of HTP use among those who intend to quit 2 . While 4.9% of HTP users in our study intended to quit, other studies have also reported relatively lower proportions of smokers who use HTPs and plan to quit smoking; for instance, 4.3% in Korea 10 and 16.9% in Europe 34 . Moreover, in this last study, only 2% of smokers who intend to quit smoking reported using HTPs as a cessation aid 34 .…”
Section: Discussioncontrasting
confidence: 81%
“…While 4.9% of HTP users in our study intended to quit, other studies have also reported relatively lower proportions of smokers who use HTPs and plan to quit smoking; for instance, 4.3% in Korea 10 and 16.9% in Europe 34 . Moreover, in this last study, only 2% of smokers who intend to quit smoking reported using HTPs as a cessation aid 34 . In our study, individuals who reported both quit intentions and HTP use were no more likely to report SQAs of any duration (i.e.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In the choice of a harmonised FoP labelling system, the European Public Health Association (EUPHA) and IARC recommend a simple graded traffic-light labelling system such as the Nutri-Score, which is in use in several European countries (Box 3.7) (EHPHA, 2023 [180]; IARC, 2021 [181]). The second most common labelling system in Europe is the Keyhole marking for healthy products, established in Sweden in 1989 and subsequently adopted in Denmark, Lithuania, Norway and Iceland.…”
Section: Food Labelling Work To Affect Consumer Choice But Is Most Ef...mentioning
confidence: 99%